The Significance of Infidelity Portrayed in the Lessons in Chemistry Miniseries Adaptation - Laila Nisa'ul Khusna; Karina Hanum Luthfia (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
Novel-to-screen adaptation often produces forms of infidelity that reshape narrative structure and cultural meaning. This study examines the adaptation of Bonnie Garmus’s Lessons in Chemistry (2022) into the Apple TV+ miniseries (2023). It aims to identify how reduction, addition, and modification function in the episodic adaptation and how these changes reshape narrative meaning. Drawing on Linda Hutcheon’s adaptation theory, which views infidelity as a productive reinterpretation across media. This study employs a qualitative descriptive method through close reading of the novel and systematic viewing of all eight episodes of the miniseries. The findings reveal three major forms of infidelity. Reduction condenses several scenes and shifts psychological depth into visual expression. Addition introduces new storylines, such as the Little Miss Hastings contest and the highway protest, expanding the social and political dimensions of the narrative. Modification transforms Harriet into a politically active Black woman and redistributes Ms. Frask’s narrative role, strengthening the adaptation’s engagement with gender and racial inequality. Overall, these changes reconstruct the narrative into a broader critique of systemic oppression and make the adaptation more socially relevant to contemporary audiences.